Export Promotion: Agricultural Earnings Perspective - Babalola, Oladapo O. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
In this paper, we made use of the Ordinary Least Square method in an attempt to analyze the influence of Agricultural Export eamings on economic growth in Nigeria. Secondary data sourced from World Bank databank and Central Bank of Nigeria for 1981-2013 were used in the study. Other tests performed include the Johansen co-integration test, Augmented Dickey Fuller for stationarity, Granger Causality test to know the direction of causality of variables used. The study found out that Agricultural export as considerable spur the growth of the economy just as the Oil Sector, whereas inflation is quite negative. Hence, the study concluded that through Agricultural Export Earnings, the country can experience significant economic growth. The paper then opined that the Agricultural sector should be a top priority for policy makers. Thus, it was recommended that farmers should be encouraged through access to loan at low interest rates, incentives such as equipments and extension programmes should be given to them while not neglecting the need for human capacity development in the agricultural sector to increase expertise in agricultural practices, leading to a diversified economy.